Research on Pneumatic Muscle Position Control Based on Adaptive Backstepping Sliding Mode. Issue 1 (February 2021) - Jia, Danping; Cao, Zhi
Abstract: Aiming at the nonlinearity and uncertainty of pneumatic muscles, an adaptive backstepping sliding mode control method is proposed. Using the three-element model of pneumatic muscles, an adaptive backstepping sliding mode controller for pneumatic muscles is designed, which is proved by Lyapunov theory. For the stability of the system, a simulation test platform is built in MATLAB. The simulation results show that the designed controller has fast convergence speed and strong robustness.